Rate and Risk Factors for Conversion and Complications of Laparoscopic Cholecystectomy. - Sarker, MM; Sarker, MK; Perveen, NA (TAJ: Journal of Teachers Association, 2018)
Laparoscopic Cholecystectomy has become the gold standard for the surgical treatment of gall bladder disease, but conversion to open cholecystectomy and both operative and post operative complications are still inevitable in certain cases. Knowledge of the rate and impact of the underlying reasons for conversion and complications could help surgeons during preoperative assessment and improve the informed consent of patients. In this study we retrospectively evaluated the rate and reasons for conversion and assessed complications of our laparoscopic cholecystectomy series. We included data of 720 consecutive patients who were attempted to laparoscopic cholecystectomy between January 2008 to March 2014 at Islami Bank Medical College Hospital, Rajshahi. The study included 468 (65%) female and 252 (35%) male with mean age of 38 years (range 16-78 years). Conversion to open procedure was carried out in 58 patients with conversion rate of 8.05%. Dense and extensive adhesions were the most common reasons for conversion (21, 36. 2%). The conversion rate due to operative complications was 13.8% of all converted cases. The major operative complications were extrahepatic bile ducts injuries 2(0.3%), duodenal injury 1(0.1%), excessive bleeding 10(1.4%). The incidence of postoperative complications was 2.8%. The most common post-operative complication was wound infection (11, 1. 52%) followed by biliary leakage in 4(0.55%) patients. Delayed complications seen in our series is port site hernia (1,0.13%). Laparoscopic cholecystectomy is the preferred method even in difficult cases. Conversion from laparoscopic to open cholecystectomy should be based on the sound clinical judgment of the surgeon and not be due to a lack of individual expertise TAJ 2014; 27(2): 58-62